2016
DOI: 10.1007/s00126-015-0633-9
|View full text |Cite
|
Sign up to set email alerts
|

The Marianas-San Marcos vein system: characteristics of a shallow low sulfidation epithermal Au–Ag deposit in the Cerro Negro district, Deseado Massif, Patagonia, Argentina

Abstract: The Cerro Negro district, within the Argentinian Deseado Massif province, has become one of the most significant recent epithermal discoveries, with estimated reserves plus resources of similar to 6.7 Moz Au equivalent. The Marianas-San Marcos vein system contains about 70 % of the Au-Ag resources in the district. Mineralization consists of Upper Jurassic (155 Ma) epithermal Au- and Ag-rich veins of low to intermediate sulfidation style, hosted in and genetically related to Jurassic intermediate composition vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(6 citation statements)
references
References 62 publications
2
4
0
Order By: Relevance
“…302 Ma, Yu et al, 2020, this study) and evolved by mixing with meteoric waters at shallow levels during the mineralization process (Figure 20). This finding is consistent with many other global epithermal and subvolcanic hydrothermal deposits (e.g., Simmons, White, & John, 2005;Vidal et al, 2016;Xie et al, 2016), which have shown that meteoric waters are key contributors of the metallic elements in such deposits.…”
Section: Sources Of Ore-forming Materialssupporting
confidence: 92%
“…302 Ma, Yu et al, 2020, this study) and evolved by mixing with meteoric waters at shallow levels during the mineralization process (Figure 20). This finding is consistent with many other global epithermal and subvolcanic hydrothermal deposits (e.g., Simmons, White, & John, 2005;Vidal et al, 2016;Xie et al, 2016), which have shown that meteoric waters are key contributors of the metallic elements in such deposits.…”
Section: Sources Of Ore-forming Materialssupporting
confidence: 92%
“…Numerous occurrences of paleohot springs, represented by sinter and travertine deposits have been recognized in the Deseado Massif (Channing et al, 2007;Echeveste, 2005;Guido and Campbell, 2011, 2014Guido et al, 2002;Marchionni et al, 1999;Schalamuk et al, 1997Schalamuk et al, , 1999a. Their distribution shows that some of these paleohot springs are closely related to economic-grade deposits, such as the case of Cerro Negro (Guido and Campbell, 2012;Permuy Vidal et al, 2013), Mina Martha (Páez, 2012), Manantial Espejo (Wallier, 2009), Cerro Vanguardia (Guido and Campbell, 2014) and La Josefina (this work), among others (Fig. 1).…”
Section: Epithermal Deposits Of the Deseado Massifmentioning
confidence: 57%
“…All these characteristics indicate that the ore-forming materials (C, S, and Pb) were magmatic sources, which were derived directly from magmatic fluids and/or leached from volcanic-subvolcanic rocks by hydrothermal fluids (e.g., Akaryali & Akbulut, 2016;Vidal et al, 2016;Wang, Zeng, Zhou, Chu, & Guo, 2016).…”
Section: Mixing Of Magmatic and Meteoric Waters In Thementioning
confidence: 99%